Nilai-Nilai Pendidikan dalam Upacara Sedekah Bumi pada Desa Pucakwangi Kabupaten Pati - Septiana, Riska Angelina; Fajrie, Nur; Ismaya, Erik Aditia (Ideas Publishing, 2024)
This earth charity activity contains the essence of education that reflects the values of gratitude, respect for ancestors, and the spirit of mutual assistance, all of which contribute to strengthening relationships between people. This study aims to examine the educational values contained in the earth charity activity in Pucakwangi Village, Pucakwangi District, Pati Regency. The approach used in this study is qualitative research, which was conducted in Pucakwangi Village, Pucakwangi District, Pati Regency, Central Java Province. Data collection in this study was carried out through Observation, Interviews, and Documentation. Data analysis techniques in qualitative research were carried out during the data collection process and also after data collection was completed within a certain period of time. The findings of this study indicate that in Pucakwangi Village, Pucakwangi District, Pati Regency, the Earth Charity activity contains various educational values, including values of faith, religiosity or aspects of worship, social values, ethical values, and cultural values